Effectiveness of particle tuned mass damper devices for pile‐supported multi‐story frames under seismic excitations. Issue 11 (15th August 2020) - Liu, Shutong; Lu, Zheng; Li, Peizhen; Zhang, Wenyang; Taciroglu, Ertugrul
Summary: Particle tuned mass dampers (PTMDs) have attracted recent attention for reducing seismic demands on large structures. Yet, research on the control performance of PTMDs for soil–structure interaction (SSI) systems under earthquake excitations is non‐existent. This paper presents a comprehensive investigation on the effectiveness of PTMD devices for pile‐supported multistory frames through shaking table tests and simulations with validated numerical models. Particle damping effectiveness is analyzed through comparisons with systems lacking external damping. The test results show that the mitigation effects of PTMDs on the maximum structural accelerations and displacements decrease when SSI effects are present and that particle damping improves control performance of conventional TMDs. Detailed finite element models of the tested specimens are also constructed—including SSI effects—and validated initially against the test data. In these models, the soil nonlinearities are considered using a bounding surface plasticity model, and the PTMD devices are simplified to an equivalent single‐particle damper using an analytical model. The validated numerical models can be used in further parametric studies involving optimal PTMD design and deployment within a performance‐based seismic engineering framework.